Art, face and breathscape: From air to cultural texts - Barbotto, Silvia (Sign Systems Studies, 2021)
We consider breath as a vast prospect that includes actions and traces of them, that builds images and texts, that involves the human being and the extra-human context; we call this great scenery ‘breathscape’. We then study how breathscape interacts with the human apparatus of the face, both giving rise to signs, but also giving rise to a liminal zone of extremely intriguing interpretative processes on a mereological scale. How and where do the territory of breath and the body interact? Which processes of signification do they give rise to? And which signs are created in their phenomenal and semantic encounter? Art is certainly the most appropriate language for studying this process, as well as for letting opacities emerge and exploring outstanding contrasts. There are various concepts of ‘breathscape’ that, grounded in different cultures, are immediately associated with ancient and contemporary philosophies. As a reverberation from a semiotic interaction and through the discretization and identification of semantic fields relevant to the concerned scenario, and introducing textuality, a phenomenon seen as a crystallization of the transition between outer text (the text of reality) and text (subject/object), we consider those visual texts which are crossed by a common faculty that is both descriptive and inventive: by approaching some inferential and cultural regimes and analysing their specific enunciative practices, we then contribute to their renovation. The texts related to the practices as part of the narratives intrinsic to cultural semiospheres underline the insatiable vastness of epistemological content to be dealt with, and the functional reductionism of the corpus is only a first approach to the field that is intended to shed light on the general panorama and to stimulate subsequent debate and insights.